Congenital toxoplasmosis infection in an infant born to an HIV-1-infected mother - Maria Letícia Santos Cruz; Claudete Araújo Cardoso; Mariza C. Saavedra; Eliane dos Santos; Tatiana Melino (Brazilian Journal of Infectious Diseases)
We report the occurrence of congenital toxoplasmosis in an infant born to an HIV infected mother who had high anti-toxoplasma IgG and negative IgM at nine weeks of gestation. We briefly review available literature and discuss the possible mechanisms of transmission of congenital toxoplasmosis among HIV infected pregnant women.